High activity of human cytomegalovirus in patients with Sjögren's disease - Pantalone, Mattia Russel; Xu, Xinling; Almazán, Nerea Martín; Gerstner, Christina; Fischer, Marie; Kvarnström, Marika; Söderberg-Nauclér, Cecilia; Wahren-Herlenius, Marie; Rahbar, Afsar (Elsevier BV, 2025)
Sjögren's disease (SD) is a chronic autoimmune disease characterized by immune-mediated damage to salivary and lacrimal glands. This study aimed to explore the potential link between SD and human cytomegalovirus (HCMV), by analyzing presence of HCMV proteins in salivary gland tissue specimens and prevalence of HCMV-specific antibodies in serum samples from SD patients and controls. HCMV-immediate early (IE) and late proteins (LA and pp65) were highly abundant in tissue specimens from SD patients (88.9 %, 69.2 %, 45.8 %, respectively), and less abundant in patients with Sicca symptoms without SD (70.5 %, 20.0 %, 12.5 %, respectively). Samples in the SD group were also positive at higher scores for the HCMV proteins than Sicca symptom patients without SD. IgM prevalence was higher in SD patients than in healthy controls (32.1 % vs. 13.4 %, P = 0.04) and HCMV-IgG titers were higher (P < 0.0001). Understanding the potential role of HCMV in SD pathogenesis may contribute to advancements in disease prevention and treatment.